1999
DOI: 10.1073/pnas.96.22.12406
|View full text |Cite
|
Sign up to set email alerts
|

RNase E is required for the maturation of ssrA RNA and normal ssrA RNA peptide-tagging activity

Abstract: During recent studies of ribonucleolytic ''degradosome'' complexes of Escherichia coli, we found that degradosomes contain certain RNAs as well as RNase E and other protein components. One of these RNAs is ssrA (for small stable RNA) RNA (also known as tm RNA or 10Sa RNA), which functions as both a tRNA and mRNA to tag the C-terminal ends of truncated proteins with a short peptide and target them for degradation. Here, we show that mature 363-nt ssrA RNA is generated by RNase E cleavage at the CCA-3 terminus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
83
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 48 publications
1
83
0
Order By: Relevance
“…Since the degradation of T4 mRNA in a stage-dependent manner would require timely and quantitative expression of genes at former stages (Kai et al, 1998;Ueno and Yonesaki, 2001), it may be possible that an rne mutation affects T4 mRNA degradation via gene expression. Furthermore, RNase E also takes a part in processing of various functional RNAs such as ribosomal RNAs (Ghora and Apirion, 1978;Li et al, 1999;Wachi et al, 1999), tRNAs (Li and Deutscher, 2002;Ow and Kushner, 2002), the RNA subunit of RNase P (Lundberg and Altman, 1995) and ssrA RNA (Lin-Chao et al, 1999), all of which are essential for normal activity of protein synthesis and its quality control. Therefore, it is not clear whether the effect of RNase E on T4 mRNA turnover is direct or indirect.…”
Section: Introductionmentioning
confidence: 99%
“…Since the degradation of T4 mRNA in a stage-dependent manner would require timely and quantitative expression of genes at former stages (Kai et al, 1998;Ueno and Yonesaki, 2001), it may be possible that an rne mutation affects T4 mRNA degradation via gene expression. Furthermore, RNase E also takes a part in processing of various functional RNAs such as ribosomal RNAs (Ghora and Apirion, 1978;Li et al, 1999;Wachi et al, 1999), tRNAs (Li and Deutscher, 2002;Ow and Kushner, 2002), the RNA subunit of RNase P (Lundberg and Altman, 1995) and ssrA RNA (Lin-Chao et al, 1999), all of which are essential for normal activity of protein synthesis and its quality control. Therefore, it is not clear whether the effect of RNase E on T4 mRNA turnover is direct or indirect.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies revealed that RNase E controls the stability of many (8, 9), if not most, mRNAs in Escherichia coli (3), as well as being involved in the processing of 5S and 16S rRNAs (1,20,32), tRNA precursors (19) and degradation of small regulatory RNAs (21). Moreover, RNase E has the ability to affect protein degradation through its role in maturation of the 3' end of tmRNA (SsrA) (22).Purification studies have revealed that in E. coli RNase E forms a large multienzyme complex referred to as 'degradosome ' (5, 24, 26). In addition to RNase E, the other major components of this complex are polynucleotide phosphorylase (pnpase), enolase and RhlB RNA helicase.…”
mentioning
confidence: 99%
“…Subsequent studies revealed that RNase E controls the stability of many (8, 9), if not most, mRNAs in Escherichia coli (3), as well as being involved in the processing of 5S and 16S rRNAs (1,20,32), tRNA precursors (19) and degradation of small regulatory RNAs (21). Moreover, RNase E has the ability to affect protein degradation through its role in maturation of the 3' end of tmRNA (SsrA) (22).…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11]. The multicomponent complex consists of: the RNA endonuclease RNase E, whose activity is essential for Escherichia coli cell growth (12)(13)(14), RNA processing (15,16), and degradation (17,18); the 3Ј-5Ј exoribonuclease PNPase (19); RhlB RNA helicase (20); and enolase (21), an enzyme involved in the glycolytic pathway and other chaperonin proteins (3,22). Interestingly, in addition to mRNAs, highly structured, stable RNA fragments have also been found to be associated with RNA degradosome complexes (3,23), which implies quality control by the RNA degradosome for the biogenesis of stable RNAs.…”
mentioning
confidence: 99%